Hubungan Perilaku Hygiene Dengan Kejadian Diare Pada Anak Di Puskesmas Tegalrejo - Audini, Aringga; Istiqomah; Suminar, Istinengtiyas (Sahabat Publikasi Kuu, 2024)
Introduction : One of the risk factors that causes diarrhea is hygiene behavior. Behavior is a person's action in responding to something and then making it a habit, while hygiene is a health effort by maintaining and protecting cleanliness. This study aims to determine the relationship between hygiene behavior (defecation behavior, snacking behavior, hand washing behavior and nail cleanliness behavior) with the incidence of diarrhea in children at the Tegalrejo Community Health Center.Method: This research is a quantitative study with a correlation design and uses a cross-sectional approach. The research subjects were 105 school-aged children (6-18 years) at the Tegalrejo Community Health Center with samples taken using the Purposive Sampling technique. Data collection was measured using a questionnaire which was analyzed using Chi-Square Test. Result: In this study there was no relationship between defecation behavior and the incidence of diarrhea with p value = 0.265 (p>0.05), there is a significant relationship between behavior snacks and the incidence of diarrhea with p value = 0.000 (p<0.05), there is a significant relationship between hand washing behavior and the incidence of diarrhea with p value = 0.000 (p<0.05), there is a significant relationship significant relationship between maintaining nail cleanliness and the incidence of diarrhea with p value = 0.000 (p<0.05). Conclusions: Based on the research results, there is no relationship between defecation behavior and the incidence of diarrhea and there is a relationship between the behavior of snacking, washing hands and keeping nails clean and the incidence of diarrhea.